A resilience matrix approach for measuring and mitigating disaster-induced population displacement. (January 2020) - Rand, Krista; Kurth, Margaret; Fleming, Cody H.; Linkov, Igor
Abstract: Globally, risk factors for population displacement due to major disasters are on the rise. These factors include the increasing frequency of extreme weather events, aging infrastructure, growing populations, and increasing urbanization. In cases of widespread damage, tools are needed to support complicated multiyear reconstruction efforts so that populations can return. We adapt the resilience matrix approach [1] as an organizing framework and resilience assessment tool to the problem of population displacement under conditions of damaged infrastructure. The resulting Population Resilience Matrix (PRM) links infrastructure reconstruction directly to the goal of reducing displacement due to infrastructure damage through performance metrics across the physical, social, information, and project management domains. This approach yields a summary of status and priorities that accounts for funding availability and the multi-phase recovery process. The PRM is applied to a synthetic extreme flood scenario, and includes detailed event-specific, locally relevant recovery assessment metrics. A practical approach to identifying the contributions of interdependent infrastructure systems to displacement is also outlined. The PRM is intended to support decision makers with coordinating roles, such as local disaster recovery managers. This approach is compatible with and complementary to US guidance on pre- and post-disaster planning and can also be applied internationally.